1-Hexyl-2-cyanoacrylate compound (Neucrylate) bactericidal properties. (4th October 2011) - Friedman, Peter; Casillas, Violeta; Kerber, Charles W
Abstract : Introduction: The need for medical grade tissue adhesives both in surgery and to treat trauma has become well established. Such a device has been developed and preliminary toxicity testing completed on a compounded cyanoacrylate (Neucrylate), and its properties have been modified so it may be used as an intravascular embolic agent. Given the high incidence of iatrogenic infections in hospital, it would be desirable to have such an implantable device that inhibits dangerous bacteria. Materials and method: Seven separate cultures of common bacteria were grown and exposed to Neucrylate. The impact on the exposed microorganisms was analyzed visually as well as by means of fluorescence and optical microscopy. Results: The device produced high degrees of antibacterial effect when exposed to gram positive bacteria whereas it had modest impact on gram negative bacteria.